Techno-Economic Analysis of a Marine Aquavoltaic System in Iran - Amin Momeni; Shiva Gorjian; Barat Ghobadian (AgriVoltaics Conference Proceedings)
In oil-rich countries such as the Middle East, the affordability and viability of renewable technologies and resources is hampered by the accessibility and low cost of fossil fuel resources. This represents a significant barrier to the progress and acceptance of renewable energy. The use of aquavoltaics is one of the creative measures that can solve the land and food problem and increase the attractiveness for investors. In this method, the simultaneous integration of the two systems of fish farming and photovoltaics, both of which play a crucial role in providing food security and sustainable energy, partially solves the problems of the two systems when implemented separately. The results of this research have shown that the aquavoltaic system has an annual profit of 42.32% and within 4 years the initial investment cost is returned to the investor. In addition, the aquaculture system produces 498.48 kg of Salmo Salar fish annually and the floating photovoltaic system, which consists of thin-film modules, feeds 300.85 MWh of energy into the power grid annually. The considerable profitability and shorter payback period of this project compared to the interest rates offered by Iranian banks to depositors, as well as the results of previous studies, have prompted investors to support this initiative. This in turn has encouraged the expansion of renewable energy and reduced dependence on fossil fuels.